2020
DOI: 10.21037/qims-19-962
|View full text |Cite
|
Sign up to set email alerts
|

Association between bone marrow fluorodeoxyglucose uptake and recurrence after curative surgical resection in patients with T1–2N0M0 lung adenocarcinoma: a retrospective cohort study

Abstract: Background: Evidence regarding the relationship between fluorodeoxyglucose (FDG) uptake in the bone marrow of patients with lung adenocarcinoma and prognosis is limited. This study aimed to identify whether bone marrow FDG uptake is a risk factor for recurrence in patients after curative surgical resection of T1-2N0M0 lung adenocarcinoma.Methods: From January 2012 to December 2016, we retrospectively enrolled 195 pT1-2N0M0 lung adenocarcinoma patients who underwent both preoperative FDG positron emission tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Whether PET scan might be helpful or whether circulating tumour DNA (ctDNA) analysis from peripheral blood is more sensitive should be investigated in future trials. 40 43 …”
Section: Discussionmentioning
confidence: 99%
“…Whether PET scan might be helpful or whether circulating tumour DNA (ctDNA) analysis from peripheral blood is more sensitive should be investigated in future trials. 40 43 …”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were as follows: (I) intolerance of general anesthesia or severe heart, lung, liver, and other major organ dysfunction; (II) severe coagulation disorder; (III) pregnancy; (IV) abdominal cavity or pelvic metastasis; (V) tumor perforation or acute peritonitis; or (VI) preoperative chemotherapy or radiation therapy. All participants were examined preoperatively with whole-body 18 F-FDG PET/MRI. Rectal cancer surgeries were performed according to TME principles.…”
Section: Patientsmentioning
confidence: 99%
“…Apparent diffusion coefficient (ADC) values derived from DWI are quantified and, more recently, have been considered a potential imaging parameter of tumor aggressiveness in rectal cancer (14,15). Previous studies have shown that the intensity of fluorine-18-fluorodeoxyglucose ( 18 F-FDG) uptake by malignant tumors is correlated with more aggressive tumor behavior, and high 18 F-FDG uptake in the primary tumor indicates a less favorable outcome (16)(17)(18). Recently, positron emission tomography/magnetic resonance imaging (PET/MRI) has emerged as a novel imaging technology that combines the metabolic information of PET and the anatomic and functional information of MRI in a single examination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because granulopoiesis rather than erythropoiesis strongly contributes to FDG uptake of BM and FDG uptake of BM shows a significant correlation with serum inflammatory markers, including serum C-reactive protein, neutrophil count, NLR, and PLR, the FDG uptake of BM is considered as an imaging parameter for evaluating the degree of systemic inflammatory response [ 15 , 17 , 19 , 28 , 29 ]. Furthermore, a number of studies have demonstrated a significant association between FDG uptake of BM and recurrence-free survival and OS in various malignant diseases including head and neck cancer, lung cancer, breast cancer, gastric cancer, colon cancer, and gynecologic cancer, consistently showing worse survival in patients with high BM FDG uptake [ 15 , 17 , 19 , 27 , 29 , 30 , 31 , 32 , 33 ]. In the present study, BM imaging parameters showed a significant positive association with serum inflammatory markers, and BM SUV was an independent predictor of OS in multivariable analysis after adjusting for age, sex, and TNM stage, indicating that BM SUV could have prognostic significance in patients with pancreatic cancer as well.…”
Section: Discussionmentioning
confidence: 99%